Molecular testing on endobronchial ultrasound (EBUS) fine needle aspirates (FNA): Impact of triage. Issue 2 (12th November 2017) - Sung, Simon; Crapanzano, John P.; DiBardino, David; Swinarski, David; Bulman, William A.; Saqi, Anjali
Abstract: Background: Endobronchial ultrasound (EBUS)‐guided fine needle aspiration (FNA) is performed to diagnose and stage lung cancer. Multiple studies have described the value of Rapid On‐Site Evaluation (ROSE), but often the emphasis is upon diagnosis than adequacy for molecular testing (MT). The aim was to identify variable(s), especially cytology‐related, that can improve MT. Methods: A search for EBUS‐FNAs with ROSE was conducted for lung adenocarcinomas or when this diagnosis could not be excluded. All such cases underwent reflex MT on cell blocks. The impact of cytology‐related variables [i.e., number of pass(es), dedicated pass(es) directly into media, cytotechnologist (CT), laboratory technician (LT) and triage with 1 or >1 cytologist] was evaluated. The latter category was divided into Group A [ROSE, triage and slide preparation by cytopathologist (CP) and CT at start of the procedure] and Group B (ROSE only by CT or by CT/CP after start of procedure; triage and slide preparation by CT or clinical staff). The impact of all these variables on MT was assessed. Results: A total of 100 cases were identified, and 79 had sufficient tissue for MT. Of all variables evaluated, MT was positively affected by performing a direct dedicated pass ( P  = 0.013) and ROSE by Group A ( P  = 0.033). Conclusions: ROSE with appropriate triage, including performing a dedicated pass and proper slide preparation, improves MT, and this is enhanced by having >1 cytologist at the start of the procedure. In the era of personalized medicine, "adequate" should denote sufficient tissue for diagnosis and MT.